Research of cooperative multi-stability composite energy collection with multi-frequency and broadband oscillation - Cao, Zhengxin; Yang, Renming; Hou, Mingdong; Li, Guangye (Frontiers in Materials, 2023)
Vibration energy, as a sustainable energy source, has been widely studied. However, due to the low-frequency and randomness of vibration energy, it is difficult to collect vibration energy.Therefore, how to efficiently collect vibration energy is a very challenging task. In order to expand the working bandwidth of vibration energy collection under low frequency vibration excitation, improve the energy collection efficiency with random vibration excitation, this paper studies a piezoelectric-magnetic liquid composite energy collector problem by constructing a multi-frequency cantilever structure. First, we give some theoretical analysis for the designed novel composite energy collection, and then, by several experiment results, the paper further shows the validity and advantage of the collection. Different from existing literature on the issue, combining the advantages of piezoelectric materials (piezoelectric film) and magnetic liquid, the method of the present paper not only greatly expands the working bandwidth of the vibration energy collection, but also significantly improves the energy collection efficiency. The experimental results show that the device possesses the capability of resonant energy collection in the low-frequency range (5Hz-25Hz), and can also operate effectively across the entire frequency band. Within the frequency sweep range of 5Hz-25Hz, the highest open-circuit voltage of the energy collection device can reach 21.7V, the highest instantaneous power can reach 171.61µW . Moreover, it can charge the capacitance energy of a 470µF electrolytic capacitor to 92.39µJ within 100 seconds. In some practical application scenarios, comparative experiments between the device and a existing cooperative multi-stable energy collector conducted show that the operating bandwidth increase by 296.43%, the power increase by 1012%, and the electricity generation raised to 239%, which implies that the novel composite energy collection device significantly enhances the efficiency of low-bandwidth energy collection of vibration energy.